Fenomena Kekerasan Berbasis Gender Terhadap Perempuan - Siregar, Dina Sakinah (Fakultas Hukum Universitas Islam Malang, 2024)
The pandemic condition that hit the world including Indonesia has caused various problems, one of which is the rampant cases of violence. According to the annual notes issued by the National Commission on Women, the number of violence from 2020-2021 has increased significantly by around 50%. This research explains the phenomenon of gender-based violence that occurs to women by taking data for 2020-2021. This research This research uses normative juridical research methods, using a conceptual approach and a case approach. The results of the study show that gender-based violence against women has increased, especially in the personal sphere, one of the reasons being injustice and gender inequality due to the inherent patriarchal culture in Indonesia.